Analisis Penerapan ID Card Penunggu Pasien terhadap Kepatuhan Jam Besuk di Ruang Rawat Inap Lily 1 RSU Prof. Dr. Soerojo Kota Magelang Tahun 2026 - Virgie Alfannisyah; Muadi Muadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The crowd of visitors in the inpatient room is a problem that is often encountered in Lily Room 1 RSU Prof. Dr. Soerojo Magelang has the potential to reduce the quality of service and patient safety (patient safety). The low family compliance with SPO hours visit an obstacle in creating a therapeutic care environment. This innovation project aims to improve SPO jam besuk compliance through the implementation of a visual instrument-based access system in the form of a visitor's ID Card. The method used is the PDCA (Plan, Do, Check, Action) quality management approach with intervention in the form of visitor access procedure education to nursing staff and patient's family, as well as the implementation of ID Card as a visual control media. Evaluation is carried out through field observation of the patient's family compliance level in the pre (5 days) and post (4 days) phases of the intervention. The observation results showed a significant increase in the level of visitor compliance; the previously high level of visitor capacity violations in the pre-intervention phase was drastically suppressed after the implementation of the ID Card. The conclusion of this project is that the implementation of the visitor ID Card is proven to be effective as an objective access management system in improving the discipline of besuk hours, thus creating a more orderly, quiet, and safe care environment in accordance with the hospital's Standard Operational Procedure (SPO).